The Time Cost of a Disability - Daniel S. Hamermesh; Michal Myck (Institute of Labor Economics (IZA), 2025)
We consider how a physical disability alters patterns of time use. A disability may raise the time cost of all activities; of some–making them differentially less worth doing; or it may make switching activities more costly. The first yields no predictions about time use, but the latter two possibilities both predict that fewer activities will be undertaken, with more time spent on each. These explanations describe our findings based on non-working ATUS 2008-22 respondents ages 70+, 32 percent of whom self-assess a disability. Data from the Polish Time Use Survey, where disability is medically certified, show similar results; and they demonstrate the same loss of variety over multiple days. Remarkably similar basic results are found using homogenized British, Canadian, French, Spanish, and Italian time-diaries. Overall, a mobility/physical disability leads an otherwise identical person to engage in over 10 percent fewer activities on a typical day. The lost variety represents extra costs equivalent in data from six countries to over twice the average annual income among older individuals in the country.
Keywords: J14; I10; D13; 330; time use; disability